Sex differences in functioning and disability among adults with cardiometabolic multimorbidity using Canadian longitudinal study on aging data: A cross-sectional study - Nicole I. Ketter; Isabelle Rash; Michelle C. Yang; Sarah Park; Brodie M. Sakakibara (Journal of Multimorbidity and Comorbidity)
Background Cardiometabolic multimorbidity (CM), two or more of stroke, diabetes, and heart disease is increasing in prevalence and associated with a multiplicative mortality risk. Sex differences exist in disability outcomes for those with stroke, diabetes, and heart disease, and thus are likely for those with CM. Objectives To assess 1) sex differences in the prevalence of CM, 2) sex differences in disability variables amongst those with CM, and 3) the predicted probabilities of disability among people with and without CM by sex. Methods A secondary analysis using data from the Canadian Longitudinal Study on Aging (CLSA). The CLSA included a stratified, random sample of approximately 51,000 participants aged 45 to 85 at recruitment. Independent variables include depressive symptoms, pain, high blood pressure, eyesight, limitations with activities of daily living (ADL), and social participation. Results A weighted population of 13,204,82 participants were included, 659,621 had CM. Males had a higher prevalence of CM than females, accounting for 62% of those with CM. Females with CM had a higher probability than males of reporting high depressive symptoms (females: 29% [95%CI:27%-31%], males: 21% [95%CI:19%-23%]), pain (females: 49% [95%CI:47%-52%], males: 41% [95%CI:39%-43%]), and limitations with ADL (females: 27% [95%CI:25%-29%], males: 11% [95%CI:10%-13%]) Males with CM had a higher probability than females of reporting infrequent social participation (females: 18% [95%CI:16%-20%], males: 23% [95%CI:21%-25%]). Conclusion This study provides evidence on sex differences in the likelihood of reporting disability variables in individuals with CM. These insights into sex differences can inform targeted interventions and improve patient outcomes.